Effects of Total Quality Control Practices On Employee Retention: A Study of Dangote Group of Company Limited Calabar, Cross River State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study evaluated the effects of total quality control practices on employee retention of Dangote Group of Company Calabar, Cross River State. The study employed survey research design. The population of the study was two hundred and sixty (260) respondents. The sample size for this study was one hundred and fifty-five (155) respondents from the Dangote Group of Company Limited Calabar, selected for the study using Krejcie and Morgan Table of 1970 for sample size determination. The instrument used for the study was a structured questionnaire using 4-pointLikert scales. Simple linear regression analysis model was employed to analyzed the data and test the study hypotheses. The study revealed that employee involvement had a significant effect on employees’ retention of Dangote Group of Company Limited Calabar, Cross River State. The study revealed that continuous training and education had a significant effect on employees’ retention of Dangote Group of Company Limited Calabar. Also, it was found that top management commitment had a significant effect on employees’ retention of Dangote Group of Company Limited Calabar. The study also showed that process improvement had a significant effect on employees’ retention of Dangote Group of Company Limited Calabar. The study recommended that management should allow workers to participate and contribute to quality problems and decisions in setting quality standard of the organizational products in the organization. The management of the organization should at all times train and educates the employees on new quality standards and other quality related matters or issues in order to maintain quality products and services.